Free-throw accuracy and success as a function of ball weight in 9- to 11-year-old male players Precisão e êxito em função do peso da bola em jogadores de 9 a 11 anos de idade - José Luis Arias (Universidade Estadual Paulista (UNESP), 2012)
The goal of this study was to analyze whether 9-11 years old children can attain more free-throw accuracy and success by modifying the ball weight in basketball game. The participants were 54 children (age: mean=10.63, SD=0.55 years) from six basketball teams. The participants played four games with each of the following balls: (a) standard ball weight (485 g, 69-71 cm), (b) a lighter ball (440 g, 69-71 cm), and (c) a heavier ball (540 g, 69-71 cm). The procedures adopted in the study were: (a) defining the variables, (b) instructing the observers and obtaining reliability, (c) monitoring the properties of the ball and filming the games, and (d) recording the data from the observation. The results revealed statistically significant differences for free-throw accuracy (χ²=1.76, df=2, p=.050) and success (χ²=5.69, df=2, p=.048). Free-throw accuracy and success were higher with the 440-g ball than with the 540-g ball. O objetivo deste estudo foi analisar se crianças de 9 a 11 anos poderiam alcançar maior precisão e êxito no lance livre em função de diferentes pesos da bola no basquetebol. Participaram do presente estudo 54 crianças (idade: M=10.63, SD=0.55) de seis equipes de basquetebol. Os participantes jogaram quatro jogos com cada um das seguintes bolas: (a) bola regulamentar (485 g, 69-71 cm), (b) bola menos pesada (440 g, 69-71 cm), e (c) bola mais pesada (540 g, 69-71 cm). Os procedimentos seguidos foram: (a) definição das variáveis, (b) formação dos observadores e obtenção da confiabilidade, (c) controle das propriedades da bola e filmagem dos jogos, e (d) gravação dos dados de observação. Os resultados revelaram diferenças estatísticas significativas para precisão (χ²=1,76; df=2; p=0,05) e êxito do lance livre (χ²=5,69; df=2; p=0,048). A precisão e êxito do lance livre foram mais elevados com a bola de 440 g em comparação com a bola de 540 g.